Sarcomere Structure: The Importance of Desmin Protein in Muscle Atrophy [Estructura de Sarcómera: La Importancia de Proteína Desmina en Atrofia Muscular] - Marquez-Andrade, J (Universidad de la Frontera, 2018)
Knowing the ultrastructure of skeletal muscle is critical to understand how it works under normal situation and the disorders caused by extreme or pathological conditions. Sarcomere is the basic structural unit of striated muscle tissue. An important element of sarcomere architecture are the intermediate filaments, including the desmin protein. Desmin protein contributes to maintenance of cell integrity, efficient transmission of force and mechanochemical signaling within the myocyte. Because of this, desmin protein has constantly been a focus of research that investigates its alterations associated to damage and muscle atrophy under different conditions. The purpose of the following literature review is to describe the basic concepts of muscle ultrastructure, emphasizing the desmin protein role under conditions of muscle disuse atrophy and aging. © 2018, Universidad de la Frontera. All rights reserved.